Investigations into the Addition of Herbal Methionine (Phytonin) As Substitute of Synthetic Methionine in Poultry Feeds 2-Effect of Herbal Methionine (Phytonin) Supplementation on Performance and Carcass Characteristics of Broiler Chicks - Hamid , Ibrahim I. (International Journal of Poultry Science, 2014)
This study was carried out during the period from February to March, 2014 at the Animal Production center (APRP) to investigate the replacement of the herbal methionine (HM, Phytonin) for synthetic methionine (SM) on the performance and carcass characteristics of broiler chicks. A number of 112 one day old broiler chicks Arber Ackers hybrid were used in this study and divided into 4 equal groups subdivided into 4 replicates with 7 birds each. Birds were fed a basal diet supplemented with 100:0, 50:50, 25:75 and 0:100% SM:HM for a period of 6 weeks. Experimental rations were formulated to furnish the nutrient requirements in the starter and finisher period as recommended by the National Research Council (NRC, 1994). No significant difference was observed among the dietary treatments in terms of performance indices, feed intake, body weight gain and feed conversion ratio (Kg feed per Kg gain). No significant differences were observed on carcass characteristics represented by the carcass cuts; breast, thigh, drumstick and wings as well as giblets; liver, heart and gizzard. Abdominal fat was not significantly affected, which indicates that HM Phytonin can replace partially or totally SM.